Synthesis of carbon nanocoil forests on BaSrTiO3 substrates with the aid of a Sn catalyst - Sun, J; Koos, A; Dillon, F; Jurkschat, K; Castell, M; Grobert, N (Elsevier, 2013)
A simple route for the Sn-assisted synthesis of carbon nanocoils (CNCs) by chemical vapor deposition of acetylene on polycrystalline BaSrTiO3 (BST) substrates is reported. In this study, high-quality CNC forests have been synthesized on BST substrates with the presence of Sn. The morphologies and qualities of the CNCs were characterized by scanning electron microscopy, transmission electron microscopy, and Raman spectroscopy, while the structures and compositions of catalysts were investigated by transmission electron microscopy and energy-dispersive X-ray spectroscopy. Structural control over the CNCs was achieved by simply altering the Sn concentration or acetylene flow rates. This study demonstrates that Sn can act as an efficient catalyst for CNC synthesis in conjunction with either perovskite oxides (BST) or transition metals (Fe).